PENGAWETAN SEPULUH JENIS KAYU DARI DAERAH LAMPUNG DENGAN METODE DIFUSI - Pipin Permadi; Barly Barly (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The penetration of wood preservative of ten wood species from Lampung was studied. The observation was conducted after the timber had been preserved by diffusion method. The BFCA 30% and wood samples of 6 cm by 10 cm by 200 cm were used in this experiment. The results showed that wood species has significant effect on penetration, while duration of diffusion storage period has the same effect only on keruing, damar asam, balam and cengal banglai. Eight weeks of storage was better than 4 weeks on those timber, but not for the other species. According to IUFRO classification, pulai kayu tabu and bintangur can be classified as permeable, while the others were classified as moderate.